Characterization of the Salmonella enterica Two-Component Regulatory System SsrA-SsrB and the SsrB Regulon - Mulder, David (My University, 2014)
Salmonella enterica is an intracellular bacterial pathogen of humans and the causative agent of the acute gastrointestinal disease, salmonellosis, and the chronic systemic infection, typhoid fever. Sensor proteins convert environmental signals, including signals detected within the host environment, into biochemical signals to control cellular responses. It has been previously established that the two component regulatory system SsrA-SsrB, consisting of the integral membrane sensor kinase protein SsrA and the cytoplasmic DNA-binding response regulator SsrB are essential for regulation of bacterial factors during systemic intracellular infection. The first chapter of this thesis describes characterization of the sensor kinase SsrA. The structure of the periplasmic sensor domain is modeled and evidence is presented that it is involved in enhancing signaling activity in response to environmental acidification encountered within the intracellular environment. A mechanism whereby protonation of histidine residues within this region in response to acidification drives conformational strain and thereby signaling is proposed. The second chapter describes identification of the DNA-binding motif of SsrB within regulated promoters as well as its regulon. Integration of experimental data with comparative genomics data resulted in identification of the palindromic heptameric DNA recognition motif of SsrB as well as identification of novel SsrB-regulated promoters. In addition, a DNA microarray analysis is described wherein the complete SsrB regulon is identified. Finally, the third chapter describes regulatory input of SsrB to the S. enterica type VI secretion system. This chapter also describes the contribution of this system to systemic dissemination of S. enterica during host infection. Altogether, these data advance understanding of how Salmonella controls factors essential for disease in response to the host environment during infection.
The Salmonella enterica Regulatory System SsrA-SsrB
Keywords: Salmonella; two-component regulatory system; sensor kinase; response regulator; transcription factor; regulation; secretion system; bacterial pathogenesis; regulatory evolution